Pygmy MicroRNA: Surveillance Cops in Therapy Kingdom - Utpal Bhadra; Pradipta Patra; Jagamohan Chhatai; Manika Pal-Bhadra (BMC, 2016)
Abstract MicroRNAs (miRNAs) are well preserved in every animal. These pygmy-sized (21-23 nt) noncoding RNAs scattered in the genome are responsible for micromanaging versatile gene regulation. There is involvement of miRNAs as surveillance cops in all human diseases including cardiovascular defects, tumor formation, reproductive pathways, and neurological and autoimmune disorders. The effective functional role of miRNA can be reduced by chemical entities of antisense oligonucleotides and versatile small molecules that support the views of novel therapies of different human diseases. In this study, we have updated our current understanding of designing and synthesizing miRNA-controlled therapeutic chemicals. We have also proposed various in vivo delivery strategies and discuss their ongoing challenges to combat incorporation hurdles in live cells and animals. Lastly, we have demonstrated the current progress of miRNA modulation in the treatment of human diseases to provide an alternative approach to gene therapy.